Avaliação dos níveis de frutosamina em gatos sob estresse agudo e crônico - Moraes, Lívia Fagundes [UNESP]; Thomazini, Camila Martos [UNESP]; Takahira, Regina Kiomi [UNESP]; de Carvalho, Lídia Raquel [UNESP] (My University, 2011)
Fructosamine are glycated serum proteins that are formed continuously due to the reaction between glucose and circulating proteins, and corresponding to the blood glucose control assessment over the last one to two weeks in cats. The fructosamine concentration has been used for differentiation between persistent and transient hyperglycemia. Therefore, the determination of fructosamine is considered the gold standard for monitoring glycemia into control in diabetic cats. The objective of this study was to evaluate the influence of acute and chronic stress of cats on serum fructosamine. 62 cats were selected from the Veterinary Hospital of FMVZ - UNESP, Botucatu campus. They were distributed into three groups: cats with a history of any illness or stress condition, excluding Diabetes Mellitus (DM), for a maximum of 48 hours (Group A, n = 21) or for a period exceeding 120 hours (Group B n = 27). The third group (Group C = control) was formed by 14 health cats. The groups were evaluated for serum fructosamine, glucose, protein and albumin. In this study, there was a significant increase in the values of fructosamine in animals subjected to acute and chronic stress, but these values remained within the reference range. The animals were, on average, normoglycemic, despite the positive correlation between fructosamine and glucose concentrations. We conclude that the fructosamine concentration is influenced by acute and chronic stress in cats, remaining, however, within the reference range, and therefore, still useful in the diagnosis of DM.
Assessment of fructosamine concentrations in cats with acute and chronic stress
Keywords: Cat; Fructosamine; Glicemia; Stress; Animalia